2015
DOI: 10.4238/2015.june.18.23
|View full text |Cite
|
Sign up to set email alerts
|

Identification of smut-responsive genes in sugarcane using cDNA-SRAP

Abstract: ABSTRACT. Sugarcane smut, caused by the fungus Sporisorium scitamineum, is one of the main diseases that affect sugarcane worldwide. In the present study, the cDNA-SRAP technique was used to identify genes that are likely to be involved in the response of sugarcane to S. scitamineum infection. In total, 21 bands with significant differential expression during cDNA-SRAP analysis were cloned and sequenced. Real-time qPCR confirmation demonstrated that expression of 19 of these 21 differential bands was consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
4
0
3
Order By: Relevance
“…In a recent study based on AFLP analysis, two DNA bands or markers were found to be specific to gamma-radiation induced smut-resistant mutants of sugarcane variety GT 54-9 (Esh and Nasr, 2014). The first demonstration of cDNA-SRAP method for the purpose of isolating 19 differentially expressed genes in smut-resistant sugarcane variety NCo376 under smut attack, has also been documented recently (Huang et al, 2015). Hence AFLP and cDNA-SRAP techniques are proven to be quite proficient in determining different aspects of smut resistance mechanism employed by sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study based on AFLP analysis, two DNA bands or markers were found to be specific to gamma-radiation induced smut-resistant mutants of sugarcane variety GT 54-9 (Esh and Nasr, 2014). The first demonstration of cDNA-SRAP method for the purpose of isolating 19 differentially expressed genes in smut-resistant sugarcane variety NCo376 under smut attack, has also been documented recently (Huang et al, 2015). Hence AFLP and cDNA-SRAP techniques are proven to be quite proficient in determining different aspects of smut resistance mechanism employed by sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…Analisis ekspresi gen yang berkaitan dengan ketahanan ini dapat dilakukan melalui pendekatan dengan metode molekuler seperti sequence-related amplified polymorphism (cDNA-SRAP), RT-qPCR, serta RNA-seq (Huang et al, 2015;Su et al, 2015;McNeil et al 2018). Melalui metode cDNA-SRAP, Huang et al (2015)…”
Section: Mekanisme Ketahanan Tebu Terhadap S Scitamineumunclassified
“…Molecular studies recognized specific changes in protein synthesis and identified genes that are differentially expressed during the early stage of sugarcane-S. scitamineum interaction. Many of these genes and proteins are considered to play an essential role in the host plant defense responses (Orlando et al 2005;Lao et al 2008;Que et al 2009;Huang et al 2015;Barnabas et al 2016;Singh et al 2017), but their functions are not studied in genetically different sugarcane germplasm and production environment. Also, the molecular and biochemical mechanism (s) underpinning smut resistance is not well understood (Sundar et al 2012;Sundar et al 2015).…”
Section: Introductionmentioning
confidence: 99%